Relaxing at work: does virtual reality work? An exploratory study among employees in their workplace - Michinov, Estelle; Dodeler, Virginie; Adam, Hugo; Michinov, Nicolas (Frontiers in Organizational Psychology, 2024)
The development of virtual reality provides new opportunities for conducting relaxing activities in a simulated environment. Although studies on the effects of VR-based relaxation are developing, they have mostly been performed with students, and more rarely with employees. This study aimed to examine the effects of VR relaxation exercises with employees. Forty-seven employees were divided into two conditions: Virtual Reality (n = 25) and 2D video (n = 22). The results indicate that relaxing activities reduced stress and negative emotions, while increasing perceived restoration using VR and 2D video. The acceptability and user experience were higher only in the VR condition. VR relaxation provides a sense of disconnection from the workplace that allows employees to increase the pleasant experience. The 2D solution, while less immersive, can be an alternative for employees for whom VR is not recommended. The question of inclusive digital tools is a key issue in the quality of working life programs. According to various models of stress at work (Bakker et al., 2004;Hobfoll, 2002;Lazarus and Folkman, 2020), stress is the result of an imbalance between the demands of the work situation and the resources available to employees. Both contextual (e.g., social support, family, friends and work organization) and personal resources (e.g., resilience, optimism, self-efficacy and self-control) can be used to cope with organizational demands.Stress management interventions in organizations can be classified into three categories (Cooper, 1994;Holman et al., 2018): primary (i.e., prevent stress by removing the causes), secondary (i.e., reduction and stress management) and tertiary (i.e., rehabilitation). Interventions at the secondary level are generally the most deployed, and specifically, individual-level interventions consisting in changing the behavior of individuals or coping strategies are more widely used than organizational-level interventions (